Analyzing Coping Mechanisms Among Female Students Affected by Divorce: The Role of School Guidance and Counseling - Setiyowati, Arbin Janu; Tri Hidayatullah, Hengki; Ismail, Affero (Psikopedagogia, 2024)
Divorce in marriage is often considered a solution to domestic problems; However, this can have a serious psychological impact on children, especially those in adolescence. The purpose of this study is to examine the condition of adolescent girls whose parents are divorced, identify problems that arise, and understand the coping mechanism that develops as a result. This study uses a qualitative approach with a phenomenological research design. The respondents of the study were selected by the snowball sampling technique based on certain criteria, namely adolescent girls who are high school students and their parents are divorced. The research instruments used interview guidelines and observation guidelines. Data analysis using Miles and Huberman. The findings of the study show that adolescent girls experience neglect after their parents' divorce, which leads to psychological problems such as anxiety, fear, and self-harming behavior. Adolescent girls tend to develop negative coping mechanisms, including emotional-focused coping and problem-focused coping. The results of this study are expected to be the basis for further research to develop more appropriate intervention designs in dealing with the specific challenges faced by young women in this situation